Decision support system : tools and techniques - Bandyopadhyay, Susmita (Boca Raton : CRC Press, 2023)
"This book presents different tools and techniques used for Decision Support Systems (DSS) including decision tree and table, and their modifications, multi-criteria decision analysis techniques, network tools of decision support and various case-based reasoning methods supported by examples and case studies. Latest developments for each of the technique have been discussed separately and possible future research areas are duly identified as intelligent and spatial DSS. Features: Discusses all the major tools and techniques for Decision Support System supported by examples. Explains techniques considering their deterministic and stochastic aspects. Covers network tools including GERT and Q-GERT. Explains application of both probability and fuzzy orientation in the pertinent techniques. Includes number of relevant case studies alongwith a dedicated chapter on softwares. This book aims at researchers and graduate students in information systems, data analytics, operation research including management and computer science areas"--
OCLC-licensed vendor bibliographic record.
Keywords: Decision support systems; BUSINESS & ECONOMICS / Information Management; COMPUTERS / Computer Engineering; TECHNOLOGY / Engineering / Industrial